2017
DOI: 10.1016/j.copsyc.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Gene–environment interplay in the context of romantic relationships

Abstract: A growing body of research supports an important role for genetic factors on intimate, romantic relationships. In this article, we review research that has examined the interplay between genetic and environmental influences on romantic relationships and the associations between relationship outcomes and important individual differences related to relationships. We first elaborate on how behavioral genetic and molecular genetic methods can be used to understand the etiology of relationship outcomes. We then rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…We did not find that attachment anxiety or avoidance moderated the associations between actor and partner GG genotypes and reports of marital satisfaction. Instead of providing evidence for a gene X environment model [39], we found that having the GG polymorphism of the OXTR rs53576 had a direct effect or served as a marker. To be exact, we found that one’s genetic polymorphism reflected a socially competent and empathetic disposition that is likely to lead to secure attachment which in turn leads to greater marital satisfaction.…”
Section: Discussionmentioning
confidence: 58%
“…We did not find that attachment anxiety or avoidance moderated the associations between actor and partner GG genotypes and reports of marital satisfaction. Instead of providing evidence for a gene X environment model [39], we found that having the GG polymorphism of the OXTR rs53576 had a direct effect or served as a marker. To be exact, we found that one’s genetic polymorphism reflected a socially competent and empathetic disposition that is likely to lead to secure attachment which in turn leads to greater marital satisfaction.…”
Section: Discussionmentioning
confidence: 58%
“…The goal of this section is to briefly review the types of analytic models that are typically used in genetically informed relationships research, rather than to provide an exhaustive review of specific study results (readers interested in a review of findings are referred to Whisman and South 2016). The majority of genetically informed research on relationships is conducted in twin samples, where the patterns of resemblance for monozygotic and dizygotic twins are used to make inferences about the degree to which genetic and environmental factors influence outcomes.…”
Section: Genetically Informed Research On Relationships: the Field Todaymentioning
confidence: 99%
“…Above and beyond partitioning the variance in relationship outcomes into genetic and environmental components, twin methods are also often used to examine the associations between relationship factors and other behavioral, emotional, and health outcomes (Whisman and South 2016). One common question is the nature of the associations between relationship factors and these other outcomes.…”
Section: Genetically Informed Research On Relationships: the Field Todaymentioning
confidence: 99%
“…Moreover, expressions of love and acts of affection enhance commitment (Joel et al, 2013; Marston et al, 1998) and predict stable marital bonds (Huston et al, 2001). In sum, both the emotion and expression of romantic love contribute to stable long-term relationships and positive health outcomes (see also Cacioppo et al, 2015; Foran et al, 2015; Whisman & South, 2017 for discussion).…”
Section: Introductionmentioning
confidence: 99%